Structuring of the campus community and the educational work strategies - Semen P. Bashkirov; Yakov Yu. Vasilyev (Высшее образование в России)
The article presents the categorization of student activists groups in compliance with the Herzberg’s m otivation theory that allows to s ubstantiate the m ethodological tools of educational activities completely for students motivating to the specific groups. An educational work model is expressed where the moral motivation development and the coherent use of the financial motivation are combined. Practical recommendations for the education development of the positive social motivation are made.